ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN APLIKASI KINEMASTER DI ERA PASCA NEW NORMAL PADA MATERI GREETING EXSPRESSION DI SMPN 3 CIPEUCANG - Eneng Liah Khoiriyah; Ajeng Muliyasari; Dede Imtihanudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study focused on the analysis of the use of KineMaster Application learning media in the Post New Normal era on the material about Greeting Expression which aimed to make it easier for teachers or educators to convey material to students, especially in the post-new normal era. As a medium to convey material, the KineMaster application, especially for Greeting Expressions material in the Post New Normal era, increased students’ motivation through interesting learning videos. This research was descriptive qualitative research, in which the data were collected through observation, interviews, and documents. The questionnaire was distributed to obtain data about students’ satisfaction about the material delivery through the KineMaster application. Meanwhile, the observation was used to determine the students’ attitudes and characteristics in the post-new normal era during English learning activities and the factors affecting the learning process. Then, the interview was conducted to determine the results of students' scores through this learning media. The results of this study revealed that students showed good response as evidenced by the results of the questionnaire analysis about satisfaction with a value of 89.66 and understanding of greeting expression learning through the KineMaster application learning video obtained an average score of 90.